Targeting gene expression to the head: the Drosophila orthodenticle gene is a direct target of the bicoid morphogen. - Gao, Q.; Finkelstein, R. (Development, 1998)
The Bicoid (Bcd) morphogen establishes the head and thorax of the Drosophila embryo. Bcd activates the transcription of identified target genes in the thoracic segments, but its mechanism of action in the head remains poorly understood. It has been proposed that Bcd directly activates the cephalic gap genes, which are the first zygotic genes to be expressed in the head primordium. It has also been suggested that the affinity of Bcd-binding sites in the promoters of Bcd target genes determines the posterior extent of their expression (the Gene X model). However, both these hypotheses remain untested. Here, we show that a small regulatory region upstream of the cephalic gap gene orthodenticle (otd) is sufficient to recapitulate early otd expression in the head primordium. This region contains two control elements, each capable of driving otd-like expression. The first element has consensus Bcd target sites that bind Bcd in vitro and are necessary for head-specific expression. As predicted by the Gene X model, this element has a relatively low affinity for Bcd. Surprisingly, the second regulatory element has no Bcd sites. Instead, it contains a repeated sequence motif similar to a regulatory element found in the promoters of otd-related genes in vertebrates. Our study is the first demonstration that a cephalic gap gene is directly regulated by Bcd. However, it also shows that zygotic gene expression can be targeted to the head primordium without direct Bcd regulation.